2010 International Symposium on Collaborative Technologies and Systems 2010
DOI: 10.1109/cts.2010.5478512
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the human in cyberspace: Effects of mood on trust in automation

Abstract: The present study examined the effects of mood on trust in automation over time. Participants (N = 72) were induced into either a positive or negative mood and then completed a computer-based task that involved the assistance of an automated aid. Results indicated that mood had a significant impact on initial trust formation, but this impact diminishes as time and interaction with the automated aid increases. Implications regarding trust propensity and trustworthiness are discussed, as well as the dynamic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…The positive correlation between positive integral affect and trust in technology found in this study was consistent with previous foundings with individal task performers (Merritt, 2011;Stokes et al, 2010). This study showed that the correlation still holds significance under teamwork context.…”
Section: Positive Integral Affect and Trust In Technologysupporting
confidence: 94%
See 1 more Smart Citation
“…The positive correlation between positive integral affect and trust in technology found in this study was consistent with previous foundings with individal task performers (Merritt, 2011;Stokes et al, 2010). This study showed that the correlation still holds significance under teamwork context.…”
Section: Positive Integral Affect and Trust In Technologysupporting
confidence: 94%
“…Many previous studies have found that incidental affect could influence trust (e.g., Stokes et al, 2010) and the use of technology could induce affect (e.g., Swangnetr, Zhu, Taylor, & Kaber, 2010). This study showed that both incidental affect and integral affect have effects on trust in technology.…”
Section: Implications For Designmentioning
confidence: 66%
“…For example, Xu and Montague (2013) found that group polarization happened after group discussion of the trustworthiness of the technology. Moods, which are heavily influenced by social interactions, are also found to be significantly related to trust in automation (Merritt, 2011; Stokes et al, 2010). In a meta-analysis, Hancock et al (2011) found that factors of team collaboration, such as culture, communication, and shared mental model, influence trust in robots of individuals in a team.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be due to the subjective nature of trust and the human role in making judgment about outcome integrity. A common assumption is that automated aids will increase overall productivity [6]. These researchers show that is not always the case and often the assumed performance improvements are not realized due to inappropriate reliance on automation which could be attributed to our basic understanding of trust.…”
Section: Introductionmentioning
confidence: 94%
“…In a recent study by Stokes et al [6], the effects of mood on trust in automation over time were examined. Many of the results from Merritt and Ilgen' study [23] were confirmed in Stokes et al' study.…”
Section: F Trust In Automationmentioning
confidence: 99%